The Importance of Oxidative Stress in the Development of Chronic Kidney Disease in the Context of Chronic Heart Failure - Djuraeva Nozima Orifovna (American Journal of Biomedicine and Pharmacy, 2025)
The review article presents current research data on the important role of oxidative stress in the pathogenesis of chronic kidney disease against the background of chronic heart failure as well as modern approaches to eliminate the effects of exposure to active oxygen forms and/or preventing their excessive initiation. We described the markers of oxidative stress and the modern methods of determination of the free radical oxidation and antioxidant products in various tissues.